1983
DOI: 10.1159/000198942
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Bz-Ty-PABA and the Pancreolauryl Test in the Assessment of Exocrine Pancreatic Function

Abstract: The reliability of the para-aminobenzoic acid (PABA) test (performed in the conventional manner, i.e. without control day) and of the pancreolauryl test was assayed in respect of the exocrine pancreatic capacity measured by using the secretin-caerulein test in 57 subjects, 22 of which were suffering from chronic pancreatitis. When 50 and 20% urinary excretion of the orally administered Bz-Ty-PABA and pancreolauryl, respectively, were chosen as the lower normal limits, the PABA test showed a specificity quite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Recent studies have shown a sensitivity in the range 75–100% and a specificity of 50–100% 141–152 . These rather impressive results can only be obtained in patients with advanced chronic pancreatitis.…”
Section: Fluorescein Dilaurate (Pancreolauryl) Testmentioning
confidence: 99%
“…Recent studies have shown a sensitivity in the range 75–100% and a specificity of 50–100% 141–152 . These rather impressive results can only be obtained in patients with advanced chronic pancreatitis.…”
Section: Fluorescein Dilaurate (Pancreolauryl) Testmentioning
confidence: 99%
“…The hydrolysis of this peptide results in the release of p-aminobenzoic acid, which is absorbed and excreted in urine. As this test is based on intraduodenal digestion by chymotrypsin, which is present in the pancreas in great excess, the test becomes positive only in patients with severe pancreatic insufficiency (8,9). Other screening tests for pancreatic maldigestion: The 14 C triolein and fatty acid absorption and breath tests (the first depends on duodenal lipase activity and the second on intestinal absorption) have been used to differentiate between maldigestion and malabsorption.…”
Section: Screening Tests For Pancreatic Maldigestionmentioning
confidence: 99%
“…Instead the results of the PABA and pan creolauryl tests indicate an optimal endolu minal digestion, with the exception of 2 subjects who showed urinary excretion on the borderline of pathological values. However it has been pointed out that the recovery of PABA and fluorescein in the urine might be affected by extrapancreatic factors [4,5].…”
Section: Commentmentioning
confidence: 99%
“…Both tests have been standardized [4] and their sensitivity coefficients for various lev els of digestive pancreatic insufficiency have been fairly well established and found to be good (between 70 and 100%) only for severe pancreatic insufficiencies [5,6], By measuring fecal chymotrypsin and at the same time carrying out these oral tests, a whole functional assessment of the pan creatic enzymes can be obtained. The pur pose of this study was to assess the reliability of these tests in subjects with chronic ur ticaria in whom a relationship with the digestive function, and in particular with the pancreatic function, was suspected.…”
mentioning
confidence: 99%